Development of Interested Talents Throught Training in Preparation of Scientific Writing Among Madrasah Students - Rizaldi, Dedi Riyan Rizaldi (Widyadewata, 2024)
Training on writing scientific papers has been carried out with the aim of providing an initial overview to students as new members of extracurricular teenagers scientific papers. This activity was carried out at Madrasah Aliyah Negeri 1 Mataram and was attended by all members of the extracurricular teenagers scientific papers. This training activity consists of three stages: delivery of material, assistance with the practice of preparing the introduction, and presentation of the results of student work development. The material presented in this activity consists of two topics, namely Miscellaneous Scientific Writing and Systematics of Writing Scientific Writing. Based on the training process that has been carried out, several written products have been produced by students during training activities, with titles 1). The impact of gadgets on teenagers' lives, 2). Analysis of cyber security among social media users, 3). The influence of digital technology on the behavior and thoughts of Generation Z, 4). The influence of the willow project on climate change and 5). The impact of cyberbullying on teenagers' lives.